A267 SEVELAMER-INDUCED ESOPHAGITIS: A RARE CAUSE OF SEVERE GASTROINTESTINAL INJURY. (15th March 2019) - Vantomme, E; Collins, M; Tayyari, F; Khan, K
Abstract: Background: Sevelamer is a noncalcium-containing phosphate binding medication recommended in guidelines for treatment of hyperphosphatemia in kidney disease. Common gastrointestinal side-effects include abdominal pain, dyspepsia, and vomiting, but gastrointestinal bleeding is not a recognized side effect of sevelamer. The first reported case of sevelamer-induced gastrointestinal injury was in 2013, and since then, very few cases have been described in the literature and the majority of those cases describe lower gastrointestinal bleeding. Aims: Sevelamer-induced gastrointestinal injury is a rare clinical entity, and sevelamer-induced esophagitis is an uncommon subset of this disease. We report a case of hemodynamically significant sevelamer-induced bleeding from severe esophagitis confirmed with biopsy. Methods: A new case of sevelamer-induced esophagitis was discovered in clinical practice. Results: In September 2018, a 79 year old comorbid female presented with an acute decrease in hemoglobin of 40g/L and a one day history of melena stools with a significant drop in her blood pressure. After reversal of her warfarin induced coagulopathy, an urgent endoscopy demonstrated severe circumferential esophagitis. Biopsies were taken to rule out infectious etiologies, and she was treated with PPI infusion and stabilized. Pathology confirmed the presence of "fish scale" crystals that are magenta on Ziehl-Neelsen staining and violet on periodic acid-Schiff-diastase staining, which are characteristic of sevelamer crystals. By Gomori methenamine silver staining the crystals appeared golden brown. A diagnosis of sevelamer-induced esophagitis was made. The patient improved with cessation of sevelamer without further related complications. Conclusions: Sevelamer is a rare cause of significant upper gastrointestinal injury and can be confirmed on biopsy if suspected. Sevelamer may be underappreciated as a cause of occult gastrointestinal bleeding in patients with chronic kidney disease or anticoagulation. This case highlights the necessity of further research to elucidate the true incidence of sevelamer-induced gastrointestinal injury, and the risk factors that predispose patients to developing this complication. Funding Agencies: None